SIFAT FISIK DAN MEKANIK KAYU SALAM (Syzygium polyanthum (Wight)Walp.) BERDASARKAN POSISI KETINGGIAN PADA BATANG - Erma, .; Usman, Fadiilah H; Muflihati, . (JURNAL HUTAN LESTARI, 2019)
Physical and mechanical properties of wood is one of the basic properties that need to be known in the selection of wood, because the physical and mechanical properties of wood are not the same height on the stem. Increased wood demand gives the opportunity to use wood that is not yet known for its marketing, one of which is Salam wood (Syzygium polianthum (Wight) Walp). The purpose of this research was to determine the physical and mechanical properties of Salam wood based on the height of the stem so that Salam wood can be optimally utilized by testing based on Classification SNI – 5 PKKI 1961. Methods of making test and test examples based on British Standard Methods No. 373-1957. The results showed that Salam wood has physical properties with an average  brown colour, the moisture content 3,13 % , density  0,58 kg/cm2 , Depreciation 2,59 %. Salam has mechanical properties with an average height position stem from base to tip with Modulus of Elastiscity (MOE)  97.701,54 , Modulus of Rupture (MOR) 659,18  and  Modulus Crushing  Streang 342,86 . Salam can be classified into strong class III and based on its properties and mechanics, it is suitable for use as a lightweight construction and furniture.Keywords: Density, depreciation, MCS, MOE, moisture content, MOR